Bidirectional River‐Floodplain Connectivity During Combined Pluvial‐Fluvial Events. Issue 3 (25th February 2022) - Tull, Nelson; Passalacqua, Paola; Hassenruck‐Gudipati, Hima J.; Rahman, Shazzadur; Wright, Kyle; Hariharan, Jayaram; Mohrig, David
Abstract: Hydrologic connectivity controls the lateral exchange of water, solids, and solutes between rivers and floodplains, and is critical to ecosystem function, water treatment, flood attenuation, and geomorphic processes. This connectivity has been well‐studied, typically through the lens of fluvial flooding. In regions prone to heavy rainfall, the timing and magnitude of lateral exchange may be altered by pluvial flooding on the floodplain. We collected measurements of flow depth and velocity in the Trinity River floodplain in coastal Texas (USA) during Tropical Storm Imelda (2019), which produced up to 75 cm of rainfall locally. We developed a two‐dimensional hydrodynamic model at high resolution for a section of the Trinity River floodplain inspired by the compound flooding of Imelda. We then employed Lagrangian particle routing to quantify how residence times and particle velocities changed as flooding shifted from rainfall‐driven to river‐driven. Results show that heavy rainfall initiated lateral exchange before river discharge reached flood levels. The presence of rainwater also reduced floodplain storage, causing river water to be confined to a narrow corridor on the floodplain, while rainwater residence times were increased from the effect of high river flow. Finally, we analyzed the role of floodplain channels in facilitating surface‐water connectivity by varying model resolution in the floodplain. While the resolution of floodplain channels was important locally, it did not affect as much the overall floodplain behavior. This study demonstrates the complexity of floodplain hydrodynamics under conditions of heavy rainfall, with implications for sediment deposition and nutrient removal during floods. Plain Language Summary: Unaltered river floodplains can support diverse ecosystems, reduce flooding, and remove nutrients from river water. Floodplains near the coast are particularly important, as they typically experience more frequent flooding. Floodplain function relies on a high degree of connectivity with the river, where water can move easily through the floodplain during periods of high river stage. Our study explores the ways in which heavy rainfall on a floodplain impacts this connectivity. We collected flow measurements in the Trinity River floodplain (Texas, USA) during Tropical Storm Imelda in 2019 that showed distinct flooding patterns between the rainfall and river flooding. We coupled a hydrodynamic model with a particle tracking model to see how particles in the water might move through the floodplain during the transition from rainfall‐driven to river‐driven flooding. We found that the average time a particle spent in the floodplain changed significantly after the rain in the model stopped. We also noticed that rainwater generally remained in the floodplain for much longer than river water, especially after the rain stopped. This study describes the various interactions that can occur between local rainfall and river flooding and moves toward a better understanding of sediment and nutrient transport in floodplains. Key Points: Field data and modeling show distinct signals of pluvial and fluvial flooding Floodplain residence times change dramatically between pluvial and fluvial phases of the storm Flows between river and floodplain are dominated by low points in the levee and the largest floodplain channels